Spain and NATO: financial dimension - N. A. Rostov (Ибероамериканские тетради, 2019)
The paper deals with the degree of Spanish involvement in NATO, the financial dimension of this problem is being assessed. The article analyzes the consequences of the increase in defense expenditures.